Isokinetic performance of shoulder external and internal rotators in judo and karate female elite athletes - Miodrag Drapšin; Nebojša Trajković; Dragan Atanasov; Danilo Radanović; Milka Imbronjev; Roberto Roklicer; Dejan Madić; Nebojša Maksimović; Vuk Raonić; Tatjana Trivić; Patrik Drid (University of Novi Sad, Faculty of Sport and Physical Education, 2019)
The aim of this study was to determine the isokinetic profile of shoulder internal and external rotators in judo and karate female elite athletes.; Methods: Study sample consisted of senior 13 female karate athletes (21.23 ± 2.83 years) and 13 female judokas (21.00 ± 2.51 years). For testing the isokinetic muscle strength of the external and internal rotation of the shoulder joint, the HUMAN NORM isokinetic dynamometer has been used. Testing the maximum muscle strength of subjects was carried out at an angular speed of 60º / sec and 180 º / sec; Results: Judo female athletes had higher isokinetic peak torque for right and left shoulder internal rotators than karate athletes at 60º/s and 180º/s, with a large effect size, Cohen's d = 0.89, 1.02, 0.97, 0.95, respectively. Also, large differences were observed between the judo and karate subjects in peak muscle torques of the right shoulder external shoulder rotator muscles of both limbs were greater in judokas than karate athletes. Isokinetic testing should be an integral part of training process in combat sports because in order to decrease the number of injuries and improve performance.